The Effects Of Different Plasticizers (Triacetin And Triethyl Citrate) On Polyvinyl Alcohol - Siti Aina Najian, Muhammad Zuber (Universiti Sains Malaysia, 2018)
This work aims to investigate the applicability to two different natural based plasticizers as alternative plasticizers in different types of Polyvinyl Alcohol (PVA). Two natural based plasticizers were chosen which are triacetin and Triethyl citrate as new alternative plasticizers in PVA of different hydrolysis degree (88 and 99%) but similar molecular weight and the effectiveness in term of miscibility, thermal, tensile and morphological properties were studied. The PVA and plasticizer were mixed by solvent blending method and the solution of PVA compound was casted to produce plasticized PVA film. At a fix amount of plasticizer, Differential scanning calorimetry (DSC) analysis showed that the presence of Triacetin caused reduction of glass transition temperature (Tg) and melting temperature (Tm) of both types of PVA with higher changes in 88% hydrolysis degree but with Triethyl citrate, the film showed insignificant changes of Tg and slight reduction of Tm in both types of PVA suggesting higher effectiveness of the former system. Morphology of the blends indicated phase separation of the system of PVA with Triethyl citrate thus responsible for the less effectiveness of Triethyl citrate as plasticizer of PVA. Meanwhile, thermal properties of PVA of 88% hydrolysis with different amount of Triacetin indicated that Tg continuously decreased with increasing plasticizer up to 15 wt% but then did not significantly different with 20wt% Triacetin. Tensile strength and modulus indicated slight reduction of value with increasing triacetin up to 10 wt% before sudden jump to up to around 32 MPa and 80MPa, respectively but continuous increased of elongation at break with triacetin loading. Morphological study showed significant change of morphology with rough surface in the presence of 15wt% Triacetin suggesting that the optimum loading of the plasticizer in PVA.